Potassium, rubidium and ammonium salts of μ‐(formato‐κ2O:O′)‐μ‐oxido‐bis[oxidobis(peroxido‐κ2O, O′)molybdate(VI)]. (4th January 2013) - Takehara, Masaki; Hashimoto, Masato
<x xml:space="preserve">Abstract</x> The unit‐cell parameters of the three title salts, namely, tripotassium, K3[Mo2(CHO2)O3(O2)4], trirubidium, Rb3[Mo2(CHO2)O3(O2)4], and triammonium μ‐(formato‐κ2O:O′)‐μ‐oxido‐bis[oxidobis(peroxido‐κ2O, O′)molybdate(VI)], (NH4)3[Mo2(CHO2)O3(O2)4], which were all crystallized at pH 3, are quite similar, but the potassium and rubidium salt structures are noncentrosymmetric, whereas that of the ammonium salt is centrosymmetric. Formate acts as an O:O′‐bridging ligand in the complex anion and is bound to a μ‐oxido‐bis(oxidodiperoxidomolybdate) unit.